ОСОБЛИВОСТІ ОЦІНЮВАННЯ ЯКОСТІ ПІДГОТОВКИ ФАХІВЦІВ У ЗАКЛАДАХ ФАХОВОЇ ПЕРЕДВИЩОЇ ОСВІТИ (Innovative professional education, 2022)
The assessment of the quality of professional training of specialists ininstitutions of professional preliminary higher education should be considered as alogical structure that combines four stages. Tools for evaluating the quality of specialisttraining should correspond to the objects of evaluation and the characteristics ofstudents. Evaluation criteria should correlate with the goals and tasks of the inspection.A well-founded methodology for assessing competencies and the quality ofprofessional training of specialists in colleges makes it possible to determine the reallevel of compliance of students' preparation.
Keywords: а